2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28276
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Learning and Engagement through Gamification of Student Response Systems

Abstract: Structuring classroom activities around games has been shown to increase student motivation and enjoyment. Less work has been done evaluating whether gamification benefits students in the particular context of a student response system (SRS). This evidence-based practice paper compares two SRSs, SurveyMonkey and Kahoot, to quantify the added value of gamification in enhancing student engagement during in-class problem sessions in a numerical methods course for biomedical engineering undergraduates. Students re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…as a learning tool, they bemoan challenges stifling their full engagement and participation such as technical challenges, difficulty in reading both questions and answers in the projected screen, time pressure, fear of losing and the difficulty in catching up when the wrong answer had been given. On the other hand, several researchers suggested that these challenges can create apprehension on the part of students which may have an adverse impact on students' enjoyment, motivation and concentration when undertaking the quiz (e.g., Chaiyo & Nokham, 2017;Ismail & Fakri, 2017;Tan & Saucerman, 2017;Wang 2015;Wang & Lieberoth, 2016). However, Ismail and Mohammad (2017) argue that students perceive Kahoot!…”
Section: Discussionmentioning
confidence: 99%
“…as a learning tool, they bemoan challenges stifling their full engagement and participation such as technical challenges, difficulty in reading both questions and answers in the projected screen, time pressure, fear of losing and the difficulty in catching up when the wrong answer had been given. On the other hand, several researchers suggested that these challenges can create apprehension on the part of students which may have an adverse impact on students' enjoyment, motivation and concentration when undertaking the quiz (e.g., Chaiyo & Nokham, 2017;Ismail & Fakri, 2017;Tan & Saucerman, 2017;Wang 2015;Wang & Lieberoth, 2016). However, Ismail and Mohammad (2017) argue that students perceive Kahoot!…”
Section: Discussionmentioning
confidence: 99%
“…In his TEDx talk from Feb. 2014, Zichermann says, "If we want to take advantage of the power of games, we need to collectively decide to actively put the power of games to work, to inspire creativity and innovation." [5] There are many examples of using gamification being currently used in engineering classes to benefit student learning from individual student response systems [6,7] to gamifying a learning management system for a virtual learning environment [8,9]. The authors decided to use multiple different online and physical gamified activities throughout the Fall 2017 semester in their engineering courses and observe the effectiveness of the student learning.…”
Section: Theoretical Foundation and Related Workmentioning
confidence: 99%
“…Some of these systems may also incorporate games to make learning more interesting (Jones et al 2019;Md;Yunus 2019). The games themselves may not be formative, but studies have suggested that gamified SRS is more effective than nongamified SRS in enhancing learning (Barrio, Muñoz-Organero, and Soriano 2016;Tan and Saucerman 2017) and better motivation and engagement (Wang, Zhu, and Saetre 2017).…”
Section: Learner Response System or Clickersmentioning
confidence: 99%